2016
DOI: 10.1371/journal.pone.0152461
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Moderate Exercise in Kidney of Rat after Chronic Consumption of Cola Drinks

Abstract: AimThe purpose of this study was to investigate the effect of moderate intensity exercise on kidney in an animal model of high consumption of cola soft drinks.MethodsForty-eight Wistar Kyoto rats (age: 16 weeks; weight: 350–400 g) were assigned to the following groups: WR (water runners) drank water and submitted to aerobic exercise; CR (cola runners) drank cola and submitted to aerobic exercise; WS (water sedentary) and CS (cola sedentary), not exercised groups. The aerobic exercise was performed for 5 days p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 54 publications
(48 reference statements)
9
13
0
Order By: Relevance
“…We agree that, as stated by Celec et al’ s, despite 3 months of very high daily intake of cola, the duration of their study might have been too short. Time-dependency may not only account for their negative findings on renal morphology in contrast with epidemiological evidence of cola deleterious effects on kidney and with our own recent study [ 25 ], but also for the differences in both insulin sensitivity (increased at 3 months in reference 41 vs decrease at 6 months in reference 24] and behavior, between present and previous studies [ 42 , 43 ]. We agree that there may be multiple potential reasons for discrepancies as mentioned previously [ 41 ].…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…We agree that, as stated by Celec et al’ s, despite 3 months of very high daily intake of cola, the duration of their study might have been too short. Time-dependency may not only account for their negative findings on renal morphology in contrast with epidemiological evidence of cola deleterious effects on kidney and with our own recent study [ 25 ], but also for the differences in both insulin sensitivity (increased at 3 months in reference 41 vs decrease at 6 months in reference 24] and behavior, between present and previous studies [ 42 , 43 ]. We agree that there may be multiple potential reasons for discrepancies as mentioned previously [ 41 ].…”
Section: Discussionsupporting
confidence: 63%
“…Cola drinking for 6 months, induced insulin resistance, hyperglycemia and β-cell loss with increase in α-cell fractional area [ 24 ], affected kidney morphology [ 25 ], and did not affect rat behavior in the present study. Conversely, cola drinking for 3 months reduced blood glucose levels during an oral glucose tolerance test, suggesting improved insulin sensitivity and had no effect on kidney morphology [ 42 ], and increased locomotion [ 43 ].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Histology report of this research also follows a similar pattern of nephrotoxicity; these include loss of an architectural unit of the nephron, atrophic mesangial cells, wide capsular spaces, dilated interstitial vessels and mild congestion. All these might be responsible for the leakage of urea and creatinine into the serum [49][50][51][52].…”
Section: оригінальні наукові роботиmentioning
confidence: 99%
“…19 The protective role of exercise training on renal damage has been reported in pervious works. 16,20,21 We also considered the effects of SW exercise training alone or supplemented with garlic on renal and hepatic cells apoptotic biomarkers. Interestingly, our data demonstrated that SW exercise, particularly combined with garlic supplementation, enhances the renal and hepatic Bcl-2 levels and reduces the mean value of BAX.…”
Section: Discussionmentioning
confidence: 99%